PENGARUH PENGGUNAAN DRIED DISTILLERS GRAIN WITH SOLUBLE (DDGS) PADA RANSUM BERENERGI RENDAH TERHADAP KARKAS, LEMAK ABDOMINAL, DAN HATI AYAM BROILER - Edwin Indarto; Jamhari (Jamhari); Fatimah Zahra; Zuprizal (Zuprizal); Kustantinah (Kustantinah) (Buletin Peternakan, 2011)
The experiment was conducted to find out the effect of Dried Distillers Grain with Soluble (DDGS) with low energy diet on carcass, abdomen fat and liver of broiler throughout 35 days growing period. This experiment was conducted using 125 had of day old chick. The birds were randomly devided into five dietary treatments. Each dietary treatment was assigned to five replicate pens containing five chicks. The diets contained 0, 20, 30, 40 and 50% DDGS. At 35-days old, 25 birds were weighed and slaughtered, then the carcass, abdomen fat and liver were weighed. The data were analyzed by Oneway Anova. The Duncan`s New Multiple Range Test (DMRT) were used to analyze the differences between means. There were significant effects of DDGS level on carcass weight and percentage, abdomen fat and percentage, and liver weight. Carcass weight of broiler chicken of R 0, R 20, R 30, R 40 and R 50 were 625.40±55.38, 608.60±55.61, 568.20±123.87, 422.80±55.97, and 401.80±47.53 g, carcass percentage were 61.79±1.83, 61.70±2.78, 60.17±2.57, 57.19±2.22, and 56.68±3.61%, abdomen fat weight were 15.60±3.28, 15.00±4.00, 13.20±5.63, 5.60±3.28, and 4.20±2.86 g, abdomen fat percentage were 1.56±0.42, 1.53±0.46, 1.37±0.46, 0.77±0.47, and 0.61±0.42%, and liver weight were 22.20±2.94, 21.80±3.96, 20.80±0.89, 15.80±2.77, and 15.80±1.92 g, respectively. It is concluded that the use of DDGS up to 30% could maintain the carcass, but the use of 40% DDGS decreased carcass weight and percentage, as well as the abdomen fat and liver.(Key words: Dried Distillers Grain with Soluble, Broiler chicken, Carcass, Abdomen fat, Liver)